2019
DOI: 10.28991/scimedj-2019-0103-2
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts as Triggers of Personal Growth: Post-Traumatic Growth in the Organizational Setup

Abstract: Organizational bullying and harassment constitute severe adversaries inducing trauma in their targets. As their occurrences began to proliferate alarmingly in the postmodern era, they started attracting academic and practitioner interest due to their implications for individual health and organizational productivity. More recently and coinciding with the adoption of facilitative conflict mediation methodology in organizations, incivility has increasingly been explored through the growth its consequences can po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Given these limitations and the scientific literature cited, future lines of research should address three key points: (1) the conceptual understanding of observable differences between anomalous experiences understood as attenuated psychotic hallucinations and anomalous phenomena evaluated as anomalous experiences related to ‘psi’ phenomena; (2) the statistical analysis of new psychometric properties of the MMSI-2 that identify and confirm the factorial solution presented in this report; and (3) the goodness of cut-off points that would allow evaluative decisions (though not diagnostic ones) to be made (see also Jabbari et al., 2018 ; Lappalainen, 2019 ; Van Zeebroeck, 2019 ).…”
Section: Discussionmentioning
confidence: 90%
“…Given these limitations and the scientific literature cited, future lines of research should address three key points: (1) the conceptual understanding of observable differences between anomalous experiences understood as attenuated psychotic hallucinations and anomalous phenomena evaluated as anomalous experiences related to ‘psi’ phenomena; (2) the statistical analysis of new psychometric properties of the MMSI-2 that identify and confirm the factorial solution presented in this report; and (3) the goodness of cut-off points that would allow evaluative decisions (though not diagnostic ones) to be made (see also Jabbari et al., 2018 ; Lappalainen, 2019 ; Van Zeebroeck, 2019 ).…”
Section: Discussionmentioning
confidence: 90%
“…[ 28 ] Differences in personality, values, or norms and premorbid cognitive functioning must therefore be considered. [ 29 , 16 ] These features could determine a greater susceptibility to impulsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneer scholar (Jehn, 1995) on conflict validated that team relational conflict as an interpersonal conflict generates a series of negative emotions using personal incompatibility among team members. The relational conflict has damaging consequences on cooperation and communication, which ultimately increases emotional expressions, such as counterproductive and uncivil behavior (Lappalainen, 2019). In addition, Tekleab and Quigley (2014 ) found that team relational conflict generates negative emotional expressions (i.e.…”
Section: Theoretical Foundations and Hypotheses Developmentmentioning
confidence: 99%